Directed energy deposition of γ/γ' Co-Al-W superalloys - Haußmann, Lukas; Yoo, Boryung; Jung, Chanwon; Ryou, Kenhee; Choi, Won Seok; Haußmann, Lukas; Yang, Sangsun; Boll, Torben; Neumeier, Steffen; Choi, Pyuck-Pa (Additive Manufacturing, 2022)
In this study, Co-Al-W superalloys forming γ/γ' microstructures were fabricated by laser-directed energy deposition and investigated with respect to their susceptibility to hot-cracking during manufacturing. Two alloys of different nominal compositions (Co-12Al-8W, Co-7Al-8W (at.%)) were deposited to characterize their microstructures on multiple length scales. While the as-deposited Co-12Al-8W alloy was free of cracks, the Co-7Al-8W alloy exhibited numerous cracks, particularly along high-angle grain boundaries due to internal oxidation cracking. The former Al-rich alloy showed a continuous and dense-packed Al2O3 scale on its surface, preventing internal oxidation. After homogenization heat-treatment at 1300 °C for 24 h and subsequent aging at 900 °C for 24 h, the Co-12Al-8W alloy revealed a homogeneous γ/γ' microstructure without hot-cracking. By contrast, the Co-7Al-8W alloy did not exhibit a passivation layer but only internal Al2O3 particles due to the reduced Al content and insufficiently fast transport of Al to the oxidation front. These particles acted as stress concentration and crack initiation sites during directed energy deposition, thereby limiting the printability of the Co-7Al-8W alloy. The compressive creep results reveal a similar creep resistance of crack-free Co-12Al-8W alloy compared to conventionally processed ternary Co-Al-W alloys. © 2022 Elsevier B.V.
Keywords: Additives; Alumina; Aluminum alloys; Aluminum oxide; Cobalt alloys; Creep; Creep resistance; Deposition; Grain boundaries; Heat treatment; Microstructure; Passivation; Superalloys; Ternary alloys; Co-based superalloys; Directed energy; Directed energy deposition; Energy depositions; Free of cracks; High angle grain boundaries; Hot-cracking; Length scale; Nominal composition; γ/ microstructure; 3D printers; Additive manufacturing; Co-based superalloys; Creep; Directed energy deposition; Hot-cracking